Thermoluminescence response of nanoparticles gold doped lithium borate glass subjected to photon irradiation - Obayes, Hayder Khudhair (Penerbit UTM Press, 2015)
The absorption coefficient of Borates glass is much closed to human body tissue. This fact makes borates as an ideal material for thermoluminescence material either for medical or environmental application. In this study, a glass system of 15% Li2CO3+ 85% H3BO3 doped with 0.1mol %nano-gold was prepared by using melt-quenching technique. Undoped and Au doped lithium borate glass samples were exposed to Co-60 gamma ray (1.25 MeV) with various doses ranging from 10 to 60 Gy by using Gammacell 220 excel. Various TL properties such as TL glow curve, linearity and sensitivity of the prepared glass were investigated. From the TL glow curve, it was found that the TL intensity increased by addition of Au into the glass system. The TL intensity of Au doped glass increases about 23 times higher than the undoped glass. The study also shows that the doped borate glass has a linear response subjected to Co-60 gamma irradiation at doses ranging from 10 to 60 Gy. The sensitivity of doped glass is about 22 times higher compared to un-doped glass.